Design of lattice structure for weight reduction - Hew, Jie Qi (2015)
Cellular lattice structure offers high strength together with low density, high stiffness, good impact-absorption, as well as thermal and acoustic insulation. Hence, cellular materials have become a promising class of structure for lightweight application in different fields such as aerospace, automobile and bioengineering. The advancement in additive manufacturing over the decades has helped to improve the manufacturability of the intricate designs of lattice structures. This paper focused on the structural design of lattice structure in order to fully exploit the strength of the material while at the same time reducing the weight of the overall structure. Various types of lattice structure were discussed in terms of their manufacturability using rapid prototyping and classified using Maxwell’s stability criterion. The octet truss lattice structure was selected due to its high manufacturability and potential for optimization in its mechanical properties. Possible design considerations that can influence the load mass ratio of the structure were examined. Sixteen different designs of octet truss lattice structures were derived from the proposed design considerations. Each design underwent Finite Element Analysis (FEA) simulation to evaluate the von mises stress and total displacement when the structures, made up of 2 by 2 by 2 unit cells, were loaded with forces that ranged from 20N to 100N. The load mass ratio was computed using the data to compare between the designs and assess the degree of influence of the design considerations. The findings concluded from this paper aim to serve as a guide for future work in designing lattice structure for lightweight applications.